Analysis of the performance and acceptance of real estate investment trusts (REITs) in Nigeria / Olusegun Olaopin Olanrele - Olusegun Olaopin , Olanrele (2016)
The over fifty (50) years existence of Real Estate Investment Trust (REIT) and its global adoption as a collective investment instrument for real estate sector development and growth testifies to the high return investment vehicle REIT is. The instruments in most REIT markets of America, Europe and Asia have recorded high and superior dividend yield with outstanding outperformance to their markets as widely reported by literatures and in the European Public Real Estate Association (EPRA) Global REIT surveys. The enactment of the Nigeria Investment and Securities Act (ISA) in 2007 heralded the introduction of REIT in Nigeria. However, the adoption of REIT in Nigeria in 2007 (same year with the United Kingdom and Germany) has not attracted any study either locally or internationally. The emerging African REIT regimes are yet to attract the coverage of global REIT markets surveys as well, except for the PUT & PLS of South Africa that just legislated in favour of the modern REIT. Nigeria with an economy of US$521bn in GDP, the largest in Africa, 8.5% growth rate and a population of over 170 million people presents a ready market for real estate products that can grow the property market. In the absence or availability of any study of Nigeria REIT (N-REIT) in its seven years of existence, it becomes inevitable to undertake an empirical study of the performance of Nigerian REIT. Such a study will bring Nigeria REIT to global awareness and will also be useful for the foreign direct investment decision into the Nigerian property market. The objectives of this research include assessment of N-REIT performance, identifying key factors affecting performance and their effect size on yield and an appraisal of real estate development financing as investment diversification option for N-REIT in the face of an acute shortage of development fund in the country. The research adopted mixed methods of secondary data analysis and a questionnaire survey. N-REIT outperforms the market and have low dividend but underperforms the property company. The Nigerian investors’ awareness of REIT is low resulting in low participation of both individual and institutional investors in Nigeria REIT market. There are 13 variables of influence that affect REIT return. The principal component analysis and correlation statistics reduced the variables to 5 most important variables with a significant 90% effect size as shown by the regression analysis. The study further found a diversifier benefit in real estate development financing to N-REIT at 85% and 15% real estate acquisition and financing asset allocation. The study gives an insight into Nigeria REIT market and its characteristics. The findings of the research are expected to guide investors in real estate securities of REITs, property trusts and property company shares. The limitation of the findings of this study is the REIT sample of 3 REIT companies and lack of previous study on Nigeria REIT which prevents this pioneering research from including mixed asset portfolio assessment.